2023
DOI: 10.1039/d2bm01752k
|View full text |Cite
|
Sign up to set email alerts
|

Selenadiazole derivative-loaded metal azolate frameworks facilitate NK cell immunotherapy by sensitizing tumor cells and shaping immuno-suppressive microenvironments

Abstract: The low sensitivity of tumor cells and immunosuppressive microenvironment lead to the unsatisfactory efficacy of natural killer (NK) cells immunotherapy. Here, we developed a safe and effective combination treatment by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The differences in intracellular uptake efficiency, ROS quantum yield, and photostability of IR780 and IR780-based self-assembly were the main reasons for the variation in intracellular ROS generation. Besides, extensive studies demonstrate that selenium-containing compounds could increase ROS generation, , which promoted DSe-NP with a higher fluorescence signal of DCF than DC-NP and DS-NP (3.7, 1.8 times, respectively) without laser irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The differences in intracellular uptake efficiency, ROS quantum yield, and photostability of IR780 and IR780-based self-assembly were the main reasons for the variation in intracellular ROS generation. Besides, extensive studies demonstrate that selenium-containing compounds could increase ROS generation, , which promoted DSe-NP with a higher fluorescence signal of DCF than DC-NP and DS-NP (3.7, 1.8 times, respectively) without laser irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…To address these issues, the carrier-free drug delivery system provides an alternative strategy to efficiently deliver hydrophobic drugs or PDT agents to disease sites without additional carriers through systemic circulation. , Compared with carrier-assistant drug delivery systems, a carrier-free drug delivery system with easy preparation and high drug-loading capacities avoids carrier-induced toxicity and immunogenicity, meanwhile. For designing the carrier-free drug delivery system of hydrophobic small molecules, the common strategy is that the hydrophobic drugs conjugated with carbon chains to endow them with self-aggregation behavior, but the strong intermolecular interactions of drug conjugates induce poor colloidal stability of self-assembly. , It was found that the disulfide bond could improve the spatial flexibility compared with the carbon bond which is beneficial for hydrophobic drugs to form self-assembly and improve its stability. , In addition, since selenium is in the same periodic table family as sulfur, the diselenide bond provides adequate structural flexibility for hydrophobic drug conjugates and forms a more stable self-assembly conformation . Moreover, compared with sulfur, selenium has higher oxidation responsivity owing to a weaker electron binding capacity, and selenium as an important element in the body also is found to be an antitumor agent. , Therefore, dimers conjugated by special bond-containing linkers could be a promising strategy for designing carrier-free self-assemblies of hydrophobic drugs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the wide prevalence, great harm, and emergence of drug‐resistant strains of influenza virus, it is an important task for scientists to develop new effective and multitargeted antiviral drugs. Selenadiazoles and their derivatives have been widely studied in the field of biological agents due to their rich biological activities, such as improving cellular uptake efficiency and antitumor activity, 40 promoting the effect of NK cell immunotherapy, 41 and enhancing the radiosensitivity of cancer cells 42 . However, the antiviral effect of Selenadiazole is rarely reported 43 .…”
Section: Discussionmentioning
confidence: 99%